2016
DOI: 10.1111/dom.12751
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of basal insulin peglispro and insulin glargine on liver enzymes and liver fat content in patients with type 1 and type 2 diabetes

Abstract: Aims: To compare effects of basal insulin peglispro (BIL), a hepatopreferential insulin, to insulin glargine (glargine) on aminotransferases and liver fat content (LFC) in patients with type 1 and type 2 diabetes (T1D, T2D). Materials and Methods:Data from two Phase 2 and five Phase 3 randomized trials comparing BIL and glargine in 1709 T1D and 3662 T2D patients were integrated for analysis of liver laboratory tests. LFC, measured by magnetic resonance imaging (MRI) at baseline, 26 and 52 weeks, was analyzed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 37 publications
9
59
0
Order By: Relevance
“…In insulin-naïve patients with T2D, glargine reduced LFC while BIL treatment was associated with no change. In previously insulin-treated patients with T2D, glargine had no effect while LFC increased with BIL 7. Similar results were seen in serum triglycerides, suggesting differences in lipid flux between the two insulins and different patient types 42…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In insulin-naïve patients with T2D, glargine reduced LFC while BIL treatment was associated with no change. In previously insulin-treated patients with T2D, glargine had no effect while LFC increased with BIL 7. Similar results were seen in serum triglycerides, suggesting differences in lipid flux between the two insulins and different patient types 42…”
Section: Discussionsupporting
confidence: 52%
“…BIL has different effects on LFC than glargine 7. In insulin-naïve patients with T2D, glargine reduced LFC while BIL treatment was associated with no change.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The primary LFC and routine blood lipid results are reported elsewhere [8, 11]. Here we report the results of the lipoprotein particle and related lipid analyses by cohort (type 1 diabetes, type 2 insulin naïve, or type 2 previously on insulin) and treatment (insulin glargine or BIL) at baseline and follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in particle size of LDL, HDL, and VLDL were also compared. The objectives and results of the LFC study have been reported elsewhere [11, 12]. …”
Section: Introductionmentioning
confidence: 99%